The Rhododendron Genome and Chromosomal Organization Provide Insight into Shared Whole-Genome Duplications across the Heath Family (Ericaceae). (18th November 2019) - Soza, Valerie L; Lindsley, Dale; Waalkes, Adam; Ramage, Elizabeth; Patwardhan, Rupali P; Burton, Joshua N; Adey, Andrew; Kumar, Akash; Qiu, Ruolan; Shendure, Jay; Hall, Benjamin
Abstract: The genus Rhododendron (Ericaceae), which includes horticulturally important plants such as azaleas, is a highly diverse and widely distributed genus of >1, 000 species. Here, we report the chromosome-scale de novo assembly and genome annotation of Rhododendron williamsianum as a basis for continued study of this large genus. We created multiple short fragment genomic libraries, which were assembled using ALLPATHS-LG. This was followed by contiguity preserving transposase sequencing (CPT-seq) and fragScaff scaffolding of a large fragment library, which improved the assembly by decreasing the number of scaffolds and increasing scaffold length. Chromosome-scale scaffolding was performed by proximity-guided assembly (LACHESIS) using chromatin conformation capture (Hi-C) data. Chromosome-scale scaffolding was further refined and linkage groups defined by restriction-site associated DNA (RAD) sequencing of the parents and progeny of a genetic cross. The resulting linkage map confirmed the LACHESIS clustering and ordering of scaffolds onto chromosomes and rectified large-scale inversions. Assessments of the R. williamsianum genome assembly and gene annotation estimate them to be 89% and 79% complete, respectively. Predicted coding sequences from genome annotation were used in syntenic analyses and for generating age distributions of synonymous substitutions/site between paralgous gene pairs, which identified whole-genome duplications (WGDs) in R. williamsianum . We then analyzed other publicly available Ericaceae genomes for shared WGDs. Based on our spatial and temporal analyses of paralogous gene pairs, we find evidence for two shared, ancient WGDs in Rhododendron and Vaccinium (cranberry/blueberry) members that predate the Ericaceae family and, in one case, the Ericales order.